Semarang Local Wisdom of Creating Batik with Natural Colouring for Tourism Industry - Mutiara, Athaya; Sundari, Wiwiek (2023)
Culture is preserved by keeping its practice so that it will not be forgotten, replaced, or gone. Culture existence shows the society’s effort in preserving a cultured life. Batik is one of Javanese culture reflecting their local wisdomof using natural resources for their benefit. This research shows Semarang city local wisdom in creating batik with natural colouring for tourism commercial product. It reveals the city’s effort in maintaining their culture, preserving their environment, and increasing their economy. The data were taken by doing literature review, observation, and interview, while the analysis is done by utilizing folklore research method. The result exposes that Semarang city local wisdom as Javanese is actualized in their effort of producing Batik Semarangan, managing water pollutant, and having additional income from tourism industry.